Doxorubicin as an unusual cause of organizing pneumonia - Dean, Ryan K; Subedi, Rogin; Gill, Dalvir; Lemke, Shelia (European Journal of Oncology and Environmental Health, 2017)
Organizing pneumonia is a syndrome that is characterized by respiratory illness that can be severe and life threatening. There are several well-well known causes of organizing pneumonia, including infections, environmental exposures and drugs. More specifically, there are several chemotherapeutic agents that are associated with organizing pneumonia. In addition, a very common cause is exposure to radiation in the context of radiation therapy in the treatment of breast cancer. However, in the presented case, a female with breast cancer was treated with doxorubicin in the absence of radiation therapy and developed organizing pneumonia. The cause was thought to be secondary to doxorubicin. Previously, there has only been one reported case of organizing pneumonia secondary to doxorubicin. This poses the question that perhaps drug induced organizing pneumonia, specifically secondary to chemotherapeutic agents, is more common than previously reported and the association with radiation therapy may be overestimated.